Argumentação e prova: uma situação experimental sobre quadriláteros e suas propriedades - Amorim, Márcia Cristina dos Santos (2009)
The presente work has a objective a sequence of activities which, with the help of dynamic geometry provided by the Cabri Geometry software, might empower high school students with new ways of thinking and establishing links between information and properties within a meaningful approach to mathematical reasoning. The sequence of activities is linked to the properties of a quadrilateral, which are of an empirical and exploratory nature so as to encourage a deductive approach in students. Our hypothesis is that these activities help students understand quadrilateral concepts and properties, and with the aid of the software tools, enable them to simulate and manipulate objects. Thus, these activities make for a meaningful and effective way of learning and dealing with Mathematics. It is hoped that with this sequence of activities students probe and discuss their conjectures, and put forth mathematically-grounded arguments and justifications to bear them out. The methodology adopted for the elaboration of activities is based on the principles of didactic engineering, which furnished analytical tools for the study of each activity devised. The results were examined according to Balacheff's (1988) classification of proof types. The conclusion drawn is that, thanks to all involved experimentation, manipulation and investigation, dynamic geometry has laid on a meaningful learning environment. As to reasoning and proof, it appears that students find it difficult to break free from specific cases when sustaining their arguments. Developing teaching-learning skills so as to improve construction of mathematical proof is of paramount importance